THE CORRELATION OF ENGLISH LANGUAGE LEARNERS’ E-LEARNING ANXIETY, E-LEARNING READINESS AND E-LEARNING ACHIEVEMENT - Jenuri , (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
Abstract: the era of Covid19 pandemic is where the online learning appears as an alternative learning method. the spread of virus makes reguler education stopping the face to face learning. this study aimed to find out the relationship between anxiety, readiness, and achievement in online learning. Also, this research was conducted by using correlational study. The participants of this research were the 3rd semester of students 2018 (sixth-semester students), 2019 (fourth-semester students), and 2020 (second-semester students) generation. The data were gathered through secondary data and questionnaire. findings in this study directly explained in the analysis that readiness and achievement showed no significant association, anxiety and achievement showed no significant association and also the analysis of three variables between readiness, anxiety, and achievement showed no significant association.